Analisis Manajemen Strategi Penyehatan Lembaga Pendidikan Agama Islam Dalam Meningkatkan Mutu Pendidikan Pondok Pesantren - Fikroturrohmah, Fauziyah (Addabani: Interdisciplinary Journal of Islamic Education, 2024)
This article explains the consequences of good management of educational institution restructuring by identifying as much detailed data as possible and stating what intermediaries will be the focus of performance realization. In its discussion, this paper uses a qualitative method with data collection techniques based on library research. Based on the findings, strategic management is essential for educational institutions, companies, or organizations because, with strategic management, the direction of an institution will be directed, and the goals will be achieved quickly. Meanwhile, the strategic implementation of restructuring in Islamic educational institutions will only run well with careful planning.